IMPLEMENTASI INTRUSION DETECTION SYSTEM (IDS) PADA SERVER DEBIAN MENGGUNAKAN JEJARING SOSIAL SEBAGAI MEDIA NOTIFIKASI - Budiman, Sahid Aris; Iswahyudi, Catur; Sholeh, Mohammad (Jurnal Jarkom, 2014)
ABSTRACTIntrusion Detection System (IDS) is a software that can detect suspicious activity in a system or network . IDS can inspect inbound and outbound traffic in a system or network, analyzing and searching for evidence of trial intrusion. Implementation of IDS on the server using social networking (facebook, twitter, and whatsapp) as notification media makes it easy for administrators identifying infiltration attempt by parties who are not responsible. Social networking on a system is built to serves to provide notifications to administrators as soon as possible when an attack occurred on the server. A message sent contains the IP address of hosts are detected by the system. Client later attacks by IDS snort stored into a MySQL database , at the same time in automatic trigger will run iptables already defined and send notifications to social networks based on the type of attack that performed by the intruder. Based on the test, the system is capable to processing output data from Snort IDS and it can also recognize all activities conducted an intruder in attempt to infiltrate into the system by using the ping flood, syn attack, port scanner, the SSH and FTP based on rules has been applied. Then do the blocking of IP addresses that are considered as intruder after that the system will provide a report to the administrator through social media and web monitoring of the presence of an intruder who trying to get into the system.Keywords: IDS, snort, social networking